GLACIATIONS OF THE EAST EUROPEAN PLAIN-DISTRIBUTION AND CHRONOLOGY - Velichko A.A.; Faustova M.A.; Gribchenko Y.N.; Pisareva V.V.; Sudakova N.G. (My University, 2004)
The quaternary chronology and distribution of glaciations through the last million years is described. The scheme of main paleogeographical events is based on multidisciplinary studies (geological, paleontological, palynological and paleopedological evidences). Succession of glaciations - Don (the maximum one), Dnieper (with Moscow Stage), and Valdai - shows a consistent reduction of ice sheets sizes and westward displacement of their centers due to climatic reasons. The extreme cooling, as well as the maximum permafrost expansion occurred at the end of the Pleistocene (MIS 2).
Keywords: Cenozoic::Quaternary; Кайнозой::Четвертичная